A note on increased intake in lambs through diversity in food flavour - Distel, Roberto Alejandro (2006)
Because preferences for food flavor decline during and after a meal, intake could be increased by offering the same food in different flavors simultaneously. The objective of this study was to determine the effects of offering the same hay with different flavors on forage intake by lambs. Individually penned lambs were given ad libitum access to either alfalfa hay (Trial 1) or pasture (alfalfa-grass) hay (Trial 2). In both trials, lambs in the variety of flavors (VF) treatment were simultaneously fed the same amount of natural, garlic, oregano, and basil flavored hay, whereas lambs in the natural flavor (NF) treatment were fed natural hay. There was no difference (P > 0.05) between treatments in daily intake of alfalfa hay in Trial 1 (mean daily intake ± S.D. was 1620 ± 234 g for VF and 1583 ± 262 g for NF). In Trial 2 lambs in the VF treatment ingested 10% more (P < 0.07) pasture hay than lambs in the NF treatment (mean daily intake ± S.D. was 1446 ± 181 g for VF and 1320 ± 214 g for NF). Variety of flavor tended to increase consumption of pasture hay (middle quality hay), but did not increase consumption of alfalfa hay (high quality hay).